ANALISIS IMPLEMENTSI PROGRAM GERAKAN LITERASI DAN NUMERASI PESERTA DIDIK DI UPTD SD NEGERI PAILELANG - Yohanis Duil; Nehemia Fanpada (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This study aims to describe the planning, implementation, and the supporting and inhibiting factors of the Student Literacy and Numeracy Movement Program at UPTD SD Negeri Pailelang. The study employs a qualitative approach with a descriptive method. The research subjects consist of the school principal and teachers. Data collection techniques included observation, interviews, and documentation, while data analysis involved data reduction, data presentation, and conclusion drawing, with validity verified through triangulation. The results indicate that the planning of the literacy and numeracy program is carried out by formulating a school program integrated into learning activities. Implementation involves a 15-minute reading session prior to the start of lessons, the execution of the School Literacy Movement stages (habituation, development, and learning), and the application of numeracy activities during classroom instruction. The program has proceeded successfully and has positively impacted the improvement of students' reading habits and numeracy skills. Supporting factors for the program include the availability of reading materials, principal support, teacher commitment, and student participation. Meanwhile, inhibiting factors identified include limited facilities and infrastructure, budget constraints, and a lack of parental support in fostering a literacy culture at home.